Basic motor movements of elementary school students following their experience with online learning during the COVID-19 pandemic period - Sunanto,; Himawan, Agus; Purwoto, Septyaningrum Putri; Machmudah, Machmudah; Handayani, Heni Yuli (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this quantitative-descriptive study was to assess the basic motor movements of elementary school students following their experience with online learning during the COVID-19 pandemic period. The population and sample in this study were fourth grade students of State Elementary Schools in Bangkalan District, Madura Island, East Java, Indonesia, with a total of 98 students sampled. The instrument for measuring motor skills was the Motor Ability Test for Elementary School. Followed by data collection, statistical analysis of data was processed by the SPSS program. The result showed that in the total basic motor movement in the very high category with a total of 0%, the high category was 7%, the moderate category was 87%, the low category was 4%, and very low category by 2%. The basic motor movements of elementary school students in Bangkalan, following the online learning during the COVID-19 pandemic, were categorized as moderate. Further studies are therefore needed to improve the basic motor movements of primary school children.